The address in real time data driver card for the MicroMegas detector of the ATLAS muon upgrade. (18th January 2017) - Yao, L.; Polychronakos, V.; Chen, H.; Chen, K.; Xu, H.; Martoiu, S.; Felt, N.; Lazovich, T.
Abstract: The ART Data Driver Card (ADDC) will be used in the ATLAS muon upgrade to process and transmit the Address in Real Time (ART) signals, which are generated by the front end chip (VMM) to indicate the location of the first above-threshold event. This ART signal is encoded to represent the address of the first threshold-crossing strip for trigger processing and the magnitude information is not included. The ADDC will be installed on the detector with high radiation and magnetic field thus a custom ASIC (ART ASIC) will be used to receive the ART signals from VMM and do the hit-selection processing. Processed data from ART ASIC will be transmitted out of the detector to the trigger processor through fiber connection. To evaluate the performance of the ADDC before the ART ASIC is produced, an FPGA based prototype was built. This prototype includes most of the major components of the ADDC, while a Xilinx Artix-7 FPGA is used to emulate the ART ASIC. The bench test and integration test results of this prototype will also be described.